Tutorial practices in a university training device in Mexico - León Hernández, Viridiana Aydee; Lugo Villaseñor, Elisa (Education Policy Analysis Archives, 2015)
This work presents the results of a study on the mentoring practices of the academics from an institution of higher education around mentoring and its relation to the construction of autonomous and autodidactic subjectivities in the students. This is a qualitative approach involving interviews with public university tutors. This focus on educational actors allows for the recognition of certain tutoring practices associated mainly with guidelines of a political and educational nature. Linked to the recognition of an increase in student desertion and the incorporation of training models focused on the student and learning, this approach underscores the need to integrate mentoring in educational institutions. Tutors acknowledge that their practices have modified partially with these new practices; however, the figure of the "tutor" was not yet assumed to promoting autonomy, self-directed learning, and self-training in students. From the scenario described above, we could recognize that the issue of mentoring in higher education and its ethical/educational dimension has been underserved in institutional programs, which tend to focus on retention indicators.